Festival &​ special event management (John Wiley &​ Sons Australia, 2011)
The role of marketing and communication, environmental planning, the increasing role of governments through the creation of event strategies, and the different perspectives of event management are all discussed. This edition aims to embrace and extend the growing body of knowledge relating to event management by tracking many of the recent changes and developments in the field. This offers students a current, relevant textbook for their study and professional reference.